1981
DOI: 10.3109/01485018108999323
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Variability of Concanavalin a Binding to the Plasmalemma of Human Spermatozoa

Abstract: Certain characteristics of the sperm plasmalemma were studied using 10 ejaculates from the same subject. Measurements of membrane glycoconjugates binding by FTC Con A were made on samples with equal numbers of motile spermatozoa which had been selected by migration in phosphate buffered saline (pH 7.4). Scatchard plots showed that the association constant for Con A binding to membrane glycoconjugate varied between ejaculates, but in 9 of 10 cases the number of receptor sites for this lectin was constant with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Infection by E. coli could therefore be damaging or not, depending on both intra-and inter-individual variations in the number of sperm among ejaculates (Heuchel et a l . , 1982) and intra-individual variations in the composition of the sperm cell-coat (Courtot et al, 1981). If this were also the case for bacteria other than E. coli, this would explain the contradictory data reported in the literature regarding the role of infection in subfertility of the male.…”
Section: Discussionmentioning
confidence: 99%
“…Infection by E. coli could therefore be damaging or not, depending on both intra-and inter-individual variations in the number of sperm among ejaculates (Heuchel et a l . , 1982) and intra-individual variations in the composition of the sperm cell-coat (Courtot et al, 1981). If this were also the case for bacteria other than E. coli, this would explain the contradictory data reported in the literature regarding the role of infection in subfertility of the male.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the molecules present on the surface of early spermatogenic cells are lost, modified, or replaced by newly synthesizcd cellsurface components or substances secreted by the epididy-ma1 cells [2,7,14,161. The functional role of these surface changes remains hypothetical, although it has been shown that the cell-membrane modifications involve both the protein, carbohydrate, and lipid moieties [lo, 19, 201. The changes in the carbohydrate moieties of the cell surface during epididymal passage of spermatozoa has been studied immunohistochemically with polyclonal [21,231 and monoclonal antibodies [5, 7, 8, 171. Valuable data have also been collected using lectin probes [3,15,18,22,241 for either visualization or structural analysis of cell-surface components. However, there are, as yet, no systematic studies of the cell-surface changes that occur in spermatogene-…”
Section: Introductionmentioning
confidence: 99%
“…A population of motile sperm was obtained with the swim-up method of Courtot et al [5]. Epididymal samples were recovered by surgical micropunc ture of the convoluted ducts in the distal one third of the caput and in the middle one third of the cauda regions of one epididymis of each chimpanzee, as described previously [6].…”
Section: Methodsmentioning
confidence: 99%